Immobilized Sonogashira catalyst systems: new insights by multinuclear HRMAS NMR studies - Posset, Tobias; Guenther, Johannes; Pope, Jacqueline; Oeser, Thomas; Blümel, Janet (Chemical communications, 2011)
A new chelate phosphine linker and its Pd and Cu complexes have been synthesized and immobilized. The solvent impact on these immobilized species, their mobility, and coordination preferences have been studied in situ by HRMAS (High-Resolution Magic Angle Spinning) NMR. The catalyst recycling characteristics match the HRMAS results.